Irrational Beliefs and Mental Health among Malaysian Secondary School Teachers - Shui Xian, Teo; Aisyah Panatik, Siti; Mahfar , Mastura; Mohd Azam Wan Mohd Yunus, Wan (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the association between irrational beliefs and mental health among secondary school teachers in Malaysia. A total of 82 secondary school teachers have participated in this study. Descriptive analysis and correlation analysis (r) were applied in this research. The Teachers Irrational Beliefs Scale (TIBS) was used to determine the level of irrational beliefs, while the Depression, Anxiety, and Stress Scales (DASS-21) was utilized to identify the level of depression, anxiety, and stress symptoms among the secondary school teachers. The findings showed that the level of irrational beliefs among the secondary school teachers was moderate, the level of depression and stress was normal, whereas the level of anxiety was moderate. The results showed that there was a weak, positive, significant relationship between irrational beliefs and depression, anxiety, and stress among the secondary school teachers.